Spending on military innovation in the context of basic economic doctrines: a comparative perspective on risks and benefits - Romaniv, Rostyslav (Herald of Economics, 2025)
Introduction. The war unleashed against Ukraine fundamentally changes the priorities in the formulation of the state’s economic policy. Today, the emphasis is shifting not only to increasing military spending, but also to implementing technological projects aimed at ensuring defense capability. The economic and military doctrine of the state is often based on certain economic theories and approaches, since the economy directly affects the country’s ability to maintain its defense capability, ensure the development of key sectors, and respond to external and internal challenges. Therefore, the study of various economic trends and doctrines is of critical importance for understanding how military spending and measures to increase defense capability affect the economic situation of the country as a whole. Given the complexity and multifaceted nature of this issue, it is necessary to consider the impact of military spending on key macroeconomic indicators, as well as on social and political processes, through the prism of various economic theories. Purpose. The purpose of the article is to identify a list of the main risks and benefits for the economy posed by the growth of expenditures on military innovation and defense in the context of various economic theories. Methods. To achieve the goal set in the study, statistical data from the Stockholm International Peace Research Institute (SIPRI) were used, and methods of a systematic approach, comparison, and generalization were used to formulate the main conclusions of various areas of economic theory regarding military innovations. Results. The main global trends in spending on military innovations and defense capability in general, as a basic public good, have been identified. The postulates of various areas of economic theory have been studied and their relationship to the growth of spending on military innovations and defense capability has been extrapolated. The main list of risks and benefits that arise in the process of spending on military innovations and defense capability has been formulated. Prospects for further research lie in studying the innovation policy of various leading countries in the world and the place and role of military innovations, and in developing qualitatively new approaches to organizing the financing of this process at the micro and macro levels.